The effects of magnesium and vitamin D/E co-supplementation on inflammation markers and lipid metabolism of obese/overweight population: a systematic review and meta-analysis - Deng, Kai; Liu, Jiamei; Miao, Ye; Wang, Guanqi; Wang, Xingli; Liu, Shengye; Yang, Liyu (Frontiers in Nutrition, 2025)
BackgroundInflammatory reactions can induce or facilitate the occurrence and development of various diseases in the human body. It is crucial to regulate and actively control inflammatory factors to maintain the health of an individual. Vitamins D and E and magnesium ions may potentially inhibit inflammatory responses. Abnormal lipid metabolism is known to affect people’s health and lead to serious diseases. Magnesium and vitamin E are also known to possess anti-lipidemic properties. It is worth noting that the prevalence and disease burden of some diseases are related to overweight and obesity. This systematic review and meta-analysis assesses the impact of magnesium and vitamin D or vitamin E co-supplementation on inflammation and lipid metabolism markers of obese/overweight population in randomized controlled trials (RCTs).MethodsA comprehensive search was conducted across PubMed, Web of Science, Embase and Cochrane databases until January 2024 to investigate the impact of simultaneous supplementation of magnesium and vitamin D/E. In both intervention and control groups, the research analyzed the pooled mean difference (MD) and the associated 95% confidence interval (CI) of marker levels of inflammation and lipid metabolism.ResultsMeta-analysis of nine RCTs (total of 509 individuals) showed that magnesium and vitamin D significantly elevated the levels of 25(OH)D (MD:13.37, 95%CI: 0.45, 26.29, p = 0.04) and magnesium (MD: 0.21, 95% CI: 0.16, 0.27, p < 0.00001). Co-supplementation of magnesium and vitamin D/E lowered levels of serum hypersensitivity C-reactive protein (hs-CRP) (MD: −1.19, 95%CI: −1.95, −0.42, p = 0.002). In subgroup analysis, serum levels of hs-CRP was notably reduced in individuals receiving magnesium and vitamin D supplementation (MD = −0.66, 95%CI: −1.17, −0.14, p = 0.01). However, no significant differences were observed between magnesium and vitamin E supplementation (MD: −3.54, 95%CI: −9.52, 2.43, p = 0.25). The combination of magnesium and vitamin D significantly reduced tumor necrosis factor-α (TNF-α) levels (MD: −0.87, 95%CI: −1.62, −0.11, p = 0.02). In contrast, the serum levels of interleukin-6 (IL-6) showed a non-significant decrease (MD: −0.09, 95%CI: −0.33, 0.15, p = 0.46), and did not significantly affect lipid metabolism according to levels of parameters such as serum triglyceride (MD = 1.84, 95% CI: −28.92, 32.60, p = 0.91), serum LDL-c (MD: −4.56, 95% CI: −14.19, 5.08, p = 0.35), and serum HDL-c (MD: 1.96, 95% CI: −3.07, 6.98, p = 0.45) in the co-supplementation of magnesium and Vitamin E.ConclusionThis study demonstrates a notable decrease in hs-CRP and TNF-α levels through vitamin D and magnesium co-supplementation in individuals. Particularly, middle-aged women with vitamin D deficiency, and obese or overweight participants, may experience specific benefits from vitamin D and magnesium co-supplementation in reducing inflammatory response. However, magnesium and vitamin E supplementation did not significantly reduce the indicators of lipid metabolism.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#loginpage